A Case Study on Air Combat Decision Using Approximated Dynamic Programming. (25th September 2014) - Ma, Yaofei; Ma, Xiaole; Song, Xiao
Abstract : As a continuous state space problem, air combat is difficult to be resolved by traditional dynamic programming (DP) with discretized state space. The approximated dynamic programming (ADP) approach is studied in this paper to build a high performance decision model for air combat in 1 versus 1 scenario, in which the iterative process for policy improvement is replaced by mass sampling from history trajectories and utility function approximating, leading to high efficiency on policy improvement eventually. A continuous reward function is also constructed to better guide the plane to find its way to "winner" state from any initial situation. According to our experiments, the plane is more offensive when following policy derived from ADP approach other than the baseline Min-Max policy, in which the "time to win" is reduced greatly but the cumulated probability of being killed by enemy is higher. The reason is analyzed in this paper.